2013
DOI: 10.1021/ol402549n
|View full text |Cite
|
Sign up to set email alerts
|

Transannular Diels–Alder/1,3-Dipolar Cycloaddition Cascade of 1,3,4-Oxadiazoles: Total Synthesis of a Unique Set of Vinblastine Analogues

Abstract: A powerful tandem [4+2]/[3+2] cycloaddition cascade of 1,3,4-oxadiazoles initiated by a transannular [4+2] cycloaddition is detailed. An impressive four rings, four carbon-carbon bonds, and six stereocenters are set on each site of the newly formed central six-membered ring in a cascade thermal reaction that proceeds at temperatures as low as 80 °C. The resulting cycloadducts provide the basis for the synthesis of unique analogues of vinblastine containing metabolically benign deep-seated cyclic modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Using a combination of Rh 2 (S-TCPTTL) 4 and the chiral Pybox-Ph 2 −Ho(OTf) 3 complex, the cycloadducts were obtained in a higher yield along with a good diastereoselectivity, but with reduced enantioselectivities (24− 34% ee) for both the exo-and endo-cycloadducts. By contrast, the higher enantioselectivity of the endo-cycloadduct compared with those of entries 8 and 9 and the highest endo-selectivity were observed using a combination of Rh 2 (R-TCPTTL) 4 and the chiral Pybox-Ph 2 −Ho(OTf) 3 complex (entry 10). From these results, the reduced enantioselectivity of the endocycloadduct shown in entry 9 can be attributed to the mismatched combination of the catalysts.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Using a combination of Rh 2 (S-TCPTTL) 4 and the chiral Pybox-Ph 2 −Ho(OTf) 3 complex, the cycloadducts were obtained in a higher yield along with a good diastereoselectivity, but with reduced enantioselectivities (24− 34% ee) for both the exo-and endo-cycloadducts. By contrast, the higher enantioselectivity of the endo-cycloadduct compared with those of entries 8 and 9 and the highest endo-selectivity were observed using a combination of Rh 2 (R-TCPTTL) 4 and the chiral Pybox-Ph 2 −Ho(OTf) 3 complex (entry 10). From these results, the reduced enantioselectivity of the endocycloadduct shown in entry 9 can be attributed to the mismatched combination of the catalysts.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…To evaluate the efficiency of the dual-activation methodology for the asymmetric synthesis of chiral fused indoline derivatives, we investigated the intermolecular asymmetric cycloaddition reactions between N-methylindole derivatives and six-or fivemembered cyclic carbonyl ylides derived from the corresponding diazodiketone or diazoketoester, which have not been examined for the chiral Rh(II)-catalyzed cycloadditions with indole derivatives, 13a under various combinations of achiral/ chiral Rh or achiral Cu catalysts and chiral lanthanoid metal− 2,6-bis(oxazolinyl)pyridine (Pybox) Lewis acids. Our results have revealed that the combination of Rh 2 (OAc) 4 and chiral lanthanoid Pybox Lewis acid provided the highest enantioselectivities along with high diastereoselectivities and yields.…”
Section: ■ Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The Diels-Alder reaction was applied in the total synthesis of vinblastine analogues [5], in the enantioselective total synthesis of the akuammiline alkaloid (-)-vincorine [6], and the Strychnos alkaloid (+)-minfiensine [7], as well as in the synthesis of some Aspidosperma alkaloids [8]. Rearrangement through a retro Diels-Alder reaction was observed during the investigations of (-)-criocerine [9].…”
Section: Introductionmentioning
confidence: 99%